Unconditional love [large type] : a guide to navigating the joys and challenges of being a grandparent today - Isay, Jane (Harper Luxe, an imprint of HarperCollinsPublishers, 2018)
Drawing on her personal experience, dozens of interviews, and the latest findings in psychology, Jane Isay shows how a grandparent can use his or her unique perspective and experience to create a deep and lasting bond that will echo throughout a grandchild's life. She also offers a wealth of practical advice, from when to get involved, when to stay away, and how to foster a strong relationship when you're separated by long distance.